MIGRS 13-01-001-0008 Fusion prophetic medicine (honey) and contemporary medicine (paracetamol) as a future greener pharmaceutical - Mohamed, Farahidah; Haris @ Harith, Muhammad Salahuddin; Mohd Shafri, Mohd Affendi; Doolaanea, Abd Almonem (2017)
Paracetamol or acetaminophen is a common analgesic and antipyretic drug used worldwide which available in various dosage forms such as tablet, syrup and suspension. Paracetamol suspension available in the market contains high amount of sugar to mask the bitter taste of paracetamol. High sugar content especially sucrose will lead to health problems such as dental caries especially in children who frequently have fever and colds. This study aims to explore the potential of honey to substitute sugar in paracetamol suspension. Honey is widely known as a natural sweetener. Besides, it contains micronutrients such as vitamins and enzymes that give a wholesome benefit such as antibacterial and antifungal properties. Compatibility study was performed on the API and each excipient binary mixture using differential scanning calorimetry (DSC) and supported by attenuated total reflectance (ATR). Characterisation of paracetamol honey suspension was done such as particle size, particle size distribution, zeta potential, pH and viscosity. Analgesic and antipyretic activities of the suspension compared to Panadol® were also performed on rats. Analytical methods verification of paracetamol honey suspension and 4-aminophenol were performed using HPLC. Paracetamol honey suspension was scaled up to 500 litres to identify optimum process parameters in order to manufacture a quality suspension. Samples from scale up process were taken and stored in both real time and accelerated stability chambers for stability study. Once the optimum process parameters were identified, process validation of paracetamol honey suspension was performed. All required documents were sent to National Pharmaceutical Regulatory Agency (NPRA). The paracetamol honey suspension was successfully manufactured for commercialisation. The suspension met all the compendial specification and was safe, effective and quality.